103 Great ormond street hospital digital grand rounds. (30th November 2020) - Liu, Shuang; Poisson, Justin; Willock, Marissa; Wheeler, Olivia; Smith, Jonathan
Abstract : Background: Previously attendance for face -to- face Grand Round (GR) at GOSH was 20–50. Numbers were limited by location (offsite from the main hospital), publicising the events, and perceived relevance to staff. Methods: We introduced our first digital Grand Round on 28th April 2020 as Zoom based webinars. The topics were carefully chosen to cover a wide range of subjects related to COVID-19, and we were fortunate to have speakers internally who were experts in the fields. The Q and A session was via Slido and moderated by the GR chair. Diary invites were sent to all GOSH staff in addition to the previous advertising strategies: emails and screen savers. All GRs were recorded and published on the GLA YouTube channel with consent. Results: The digital GR was met with substantial enthusiasm by GOSH staff, the attendance for the first four sessions was: 290, 501, 397 and 203. It was then between 85 and 147 in June. We did notice a considerable drop once trust email became unavailable on personal mobiles. From July, the attendance was around 35 -70. A steady increase in online viewing via GLA YouTube has been observed, with 400 views for one GR. In addition an international speaker was able to present online. Discussion: We were forced into hosting GR on a digital platform, but soon realised it could be a positive transformation in delivering trust-wide education. It has removed the geographic barrier so international presenters can attend. It does come with challenges such as maintaining interaction; the moderator's value for digital sessions is paramount. Furthermore, we should always actively look for new topics for continuous staff teaching engagement and ensure teaching information is widely accessible but secure.